Impact of Estimated Plasma Volume Status on Mortality in Right Heart Failure Patients: A Retrospective Cohort Study in Indonesia - Hannah Soetjoadi; Dewi Friska; Bambang Budi Siswanto; Hary Sakti Muliawan (Ubiquity Press, 2022)
Background: Plasma volume (PV) expansion hallmarks the syndrome of heart failure (HF) but is difficult to be quantified noninvasively. Estimated plasma volume status (ePVS) has marked prognostic utility in the failing left heart, however its use in right heart failure (RHF) remains unknown. This study aims to investigate the prognostic value of ePVS among isolated RHF patients. Methods: We retrospectively collected 208 patients admitted for RHF in our hospital from the electronic database from 2017 to 2019. ePVS was calculated using the Hakim formula. Patients were divided into low and high groups based on their PV value. Logistic regression was used to compare the odds of in-hospital mortality between these groups. Results: The overall in-hospital mortality was 12.5%, tripled from the low group to the high group (6.7% vs. 18.3%), within a median of 6 (3-19) days. High ePVS significantly predicted mortality in RHF, even after being adjusted for demographic, hemodynamic, chemistry, and medication variables (adjusted OR: 5.83, 95% CI: 1.62-20.95, 'p' < 0.01). Conclusion: ePVS is associated with in-hospital mortality among isolated RHF patients. Given not only the wide accessibility of hemogram but also the low cost and the rapid quantification of relative PV, this simple tool can potentially aid in optimizing RHF management, especially in rural area, although further evaluation is warranted.